Investigation in protective effects of Sophora pachycarpa extracts on serum level of sex hormones, urea and uric acid in carbon tetrachloride-intoxicated in male rats - SM Banan Khojasteh; R Javanmard Khameneh; M Houresfand; GhR Dehghan; R Heidari; M Iranshahi (Institue of Medicinal Plants, ACECR, 2016)
Background: Carbon tetrachloride (CCl4) is an industrial solvent that causes liver, kidneys, lungs, testis and brain as well as in blood diseases by generating free radicals. Previous studies on the chemical composition of S. pachycarpa have shown the presence of antioxidant compounds such as flavonoids. Objective: In the present study we investigated protective effects of Sophora pachycarpa extracts on serum level of sex hormones, urea and uric acid in carbon tetrachloride-intoxicated in male rats. Methods: Thirty six male wistar rats (195-200 g) were selected and randomly divided into 6 groups (n=6): 3 pre-treatment groups received s.pachycarpa extract at doses 50 mg/kg/day, 100 mg/kg/day and 250 mg/kg/day by gavage for 21 days prior to intraperitoneal injection of CCl4 500 μl/kg on 21st day, control group, CCl4 group received 500 μl/kg CCl4 on the 21st day, post-treatment group received extract at doses 100 mg/kg/day for 10 day at 12h after CCl4 250 μl/kg injection. At the end of the treatment, blood was collected by cardiac puncture from all of the animals and serum levels of sex hormones, urea and uric acid were assessed. Results: Serum levels of follicle stimulating hormone was significantly increased in serum of pre-treatment group III and serum level of luteinizing hormone and testosterone in serum of pre-treatment groups compared to CCl4 was significantly increased (P<0.05). Also serum levels of urea in pre-treatment and post-treatment groups and serum level of uric acid in serum of pre-treatment II and III (100 and 250 mg/kg) was significantly decreased compared to CCl4 (P<0.05). Conclusion: Together, our data suggest that Sophora pachycarpa extract can potentially ameliorate toxic effects of CCl4.